Changes in rearfoot strike patterns over childhood : a 3-year prospective longitudinal cohort study - Latorre Román, Pedro Ángel (Array, 2021)
Rearfoot strike (RFS) in children running produces impact forces that give rise to a transient stress wave traveling through the body. It could contribute to the development of injuries. The purpose of this study was to determine RFS prevalence during childhood while running at a self-selected velocity in a prospective longitudinal cohort study. A total of 175 children (68 girls), aged 6 to 14 years, participated in this study. The sample was divided into three age groups (age in 2016): 6-8 years, 9-11 years, and 12-14 years which were analysed three years later (2019). 2D video-based was used to record the RFS Taking into account all samples, in the jogging trial the prevalence of RFS (an average of both feet) was 86.9% in 2016 and 94.7% three years later; in the running trial the prevalence was 82.6 and 94.4%, respectively.